Secondary Forest Succession and Tree Planting at the Laguna Cartagena and Cabo Rojo Wildlife Refuges in Southwestern Puerto Rico - Weaver, Peter L; Schwagerl, Joseph J (Ambio, 2008)
Secondary forest succession and tree planting are contributing to the recovery of the Cabo Rojo refuge (Headquarters and Salinas tracts) and Laguna Cartagena refuge (Lagoon and Tinaja tracts) of the Fish and Wildlife Service in southwestern Puerto Rico. About 80 species, mainly natives, have been planted on 44 ha during the past 25 y in an effort to reduce the threat of grass fires and to restore wildlife habitat. A 2007 survey of 9-y-old tree plantings on the Lagoon tract showed satisfactory growth rates for 16 native species. Multiple stems from individual trees at ground level were common. A sampling of secondary forest on the entire 109 ha Tinaja tract disclosed 141 native tree species, or 25% of Puerto Rico's native tree flora, along with 20 exotics. Five tree species made up about 58% of the total basal area, and seven species were island endemics. Between 1998 and 2003, tree numbers and basal area, as well as tree heights and diameter at breast height values (diameter at 1.4 m above the ground), increased on the lower 30 ha of the Tinaja tract. In this area, much of it subject to fires and grazing through 1996, exotic trees made up 25% of the species. Dry forest throughout the tropics is an endangered habitat, and its recovery (i.e., in biomass, structure, and species composition) at Tinaja may exceed 500 y. Future forests, however, will likely contain some exotics.